Determination of Polycyclic Aromatic Hydrocarbons in Wetland and River Waters - Abdollahi, A. (Asian Journal of Chemistry, 2013)
Polycyclic aromatic hydrocarbons are one of the most widespread groups of organic pollutants in the environment. In this work, two different solid-phase extractions, sorbents have been used. C18 and XAD-2 resin packed in micro-columns were used for separation, clean up and pre-concentration of polycyclic aromatic hydrocarbons and the recovery of polycyclic aromatic hydrocarbons from XAD-2 resin was studied and then used for pre-concentration of polycyclic aromatic hydrocarbons. The samples were collected from the river Zayandeh-Rud and Ghav-Khooni wetland in the province of Isfahan (Iran) where the heavy industries are located around the stream. The determinations were carried on a gas chromatography coupled to mass spectrometry and internal standard quantification was performed using four deuterated polycyclic aromatic hydrocarbons. For increased sensitivity, quantification was performed in the selected ion monitoring mode. In water samples of the river Zayandeh-Rud, the amounts of total polycyclic aromatic hydrocarbon ranged from west to east and the highest polycyclic aromatic hydrocarbon concentration was found in the Gav-Khooni wetland.